Teaching science and technology in the early years (3-7) - Davies, Dan (Daniel John) 1962-; Davies, Dan (Daniel John) 1962- (Routledge, 2014)
"Teaching Science and Technology in the Early Years (3-7) celebrates young children's amazing capabilities as scientists, designers and technologists. Research-based yet practical and accessible, it demonstrates how scientific, designing and making activities are natural to young children, and have the potential for contributing to all aspects of their learning. By identifying the scientific and design-related concepts, skills and activities being developed, the book enables the reader to make more focused diagnostic observations of young children and plan for how they can help move them forward in their learning. This second edition has been thoroughly updated and features:Six new chapters providing practical advice and examples for enhancing scientific and technological learning through thematic approachesa new chapter focusing on the outdoor learning environment and how this can support science and technologynew case studies of successful early years practice, alongside examples of practical planning for learning, and advice on documenting children's learning stories, guidance on the role of talk, narrative, documentation and planning in relation to early years science and technology. Based on the latest research and the first hand experience, this practical and accessible book is essential reading for early years and primary students on undergraduate and Masters level courses."--Provided by publisher.